Effect of Intensive Education and Training of Nurses on Ventilator-associated Pneumonia and Central Line-associated Bloodstream Infection Incidence in Intensive Care Unit at a Tertiary Care Center in North India - Sahni, Neeru (Indian J Crit Care Med, 2017)
OBJECTIVE: The aim was to analyze the impact of education and training of nurses on the incidence of ventilator-associated pneumonia (VAP) and central line-associated bloodstream infection (CLABSI). PATIENTS AND METHODS: A prospective observational study at a tertiary care hospital included adult patients with Intensive Care Unit stay >48 h. The study was done in three phases: in Phase 1, baseline VAP and CLABSI incidence was calculated; in Phase 2, education and training of nurses; and in Phase 3, data were recollected for the incidence of VAP and CLABSI. RESULTS: The baseline incidence of VAP in Phase 1 was 28.86/1000 ventilator days and that of CLABSI was 7.89/1000 central-line days. In Phase 3, the incidence of VAP increased to 35.06 and that of CLABSI decreased significantly, 1.73. CONCLUSION: Intensive education and training sessions with feedback from nurses over a period of 6 months led to significant reduction in the incidence of CLABSI; however, the incidence of VAP increased.